T2‐weighted turbo spin‐echo magnetic resonance imaging of canine brain anatomy at 1.5T, 3T, and 7T field strengths. Issue 1 (19th August 2021) - Jacqmot, Olivier; Van Thielen, Bert; Hespel, Adrien‐Maxence; Luijten, Peter R.; de Mey, Johan; Van Binst, Anne; Provyn, Steven; Tresignie, Jonathan
Abstract: Post‐mortem T2 weighted images of canine heads were acquired at 1.5T, 3T, and 7T. This study aimed to (1) identify anatomical structures of the canine brain using an ultra‐high‐field magnetic resonance imaging (MRI) (7T) to help to facilitate their localization on high field MRI images (3T and 1.5T), where these structures may appear less well defined and delineated and (2) evaluate the visibility of canine brain anatomical structures on 1.5T, 3T, and 7T MRI images for optimizing clinical utility. Our hypothesis was that the provided subjective image quality comparison at different field strengths may offer a general baseline for canine brain anatomy and may help clinicians evaluate MRI options better. Six canine heads were examined with 1.5T, 3T, and 7T MRI scanners. T2‐weighted images were acquired in three orthogonal planes at each field strength using a turbo spin‐echo sequence. Fifty neuroanatomic structures were identified and evaluated on the 7T MR images; subsequently, those were found on the 3T and 45 out of the 50 structures were detected on the 1.5T imaging. The structures that were not able to be identified on the 1.5T imaging included the septum pellucidum, oculomotor nucleus, substantia nigra, claustrum, and thalamic nucleus griseus . Images acquired at 7T were subjective of higher spatial and contrast resolution. However, the ultra‐high‐field images were prone to artifacts at the interface between tissues of different magnetic properties. In conclusion, 3T MR imaging appears to be the best comprise for evaluating canine brain anatomy on MRI with fewer imaging artifacts.